Dual CCR2/5 Antagonist Attenuates Obesity‐Induced Insulin Resistance by Regulating Macrophage Recruitment and M1/M2 Status. Issue 2 (27th December 2017) - Huh, Ji Hye; Kim, Hong Min; Lee, Eun Soo; Kwon, Mi Hye; Lee, Bo Ra; Ko, Hyun‐Jeong; Chung, Choon Hee
Abstract : Objective: Adipose tissue inflammation induced by macrophage infiltration through the C‐C motif chemokine receptor (CCR) 2 or CCR5 pathway has a pivotal role in obesity‐related disease and insulin resistance. Here, the effect of PF4178903, a dual CCR2/CCR5 antagonist, on obesity and insulin resistance was evaluated. Methods: Forty male C57BL/6J mice were divided into four groups as follows: (1) regular diet (RD), (2) RD with PF4178903, (3) high‐fat diet (HFD), and (4) HFD with PF4178903. All mice were sacrificed 12 weeks after the beginning of the experiment. Biochemical analyses and adipose tissue examinations were performed. Results: After treatment with PF4178903, both body weight and adipocyte size in white adipose tissue were decreased in HFD‐fed mice. Furthermore, PF4178903 treatment reduced adipose tissue macrophages (ATMs) and lowered serum proinflammatory cytokines in HFD‐fed mice. PF4178903 treatment significantly improved HFD‐induced insulin resistance and glucose intolerance. Fluorescence‐activated cell sorter analysis revealed that PF4178903 treatment reduced the CD8 + T cell fraction in white adipose tissue of HFD‐fed mice. PF4178903 treatment reduced M1‐polarized macrophages while inducing an M2‐dominant shift in macrophages within white adipose tissue in HFD‐fed mice. Conclusions: Dual CCR2/CCR5 antagonism ameliorates insulin resistance and inflammation in obesity by regulating ATM recruitment and polarization in white adipose tissue.